Penerapan Hybrid Learning Berbantuan Google Classroom Untuk Memotivasi Belajar Siswa Kelas V SD AL-Amin Surabaya - Mitha Dewi Nurmazidah; Muslimin Ibrahim; Thamrin Hidayat; Nafiah Nafiah (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2024)
Research on the application of hybrid learning assisted by Google Classroom to motivate learning for fifth grade students at SD Al-Amin Surabaya. Based on the problem that is motivated by the low motivation of student learning . This is because the teacher's delivery is often less varied during the learning process, so that students are not brave enough to communicate their thoughts. This type of research is a quantitative study with a research target of SD Al-Amin Surabaya with a total of 25 students. data collection techniques using observation and questionnaire collection. Based on the results of data analysis and discussion, the authors draw conclusions that can be drawn from this study, namely the implementation of hybrid learning assisted by Google Classroom is in the implemented category with a percentage of 100. The results of student activities on the implementation of learning can be said to be "Very Good" this is because student activity achieves a high implemented score and 11 indicators appear according to the plan in the learning lesson plan. The learning motivation of fifth grade students at SD Al-Amin Surabaya regarding the application of Google Classroom-assisted hybrid learning obtained the result "Very Good" with the results of data analysis of the total score obtained, which was 88%.